Analysis of the gut-specific microbiome from critically endangered hawksbill sea turtles (Eretmochelys imbricata) using a culture-dependent approach - Li, Hongwei; Chen, Yuan; Xia, Zhongrong; Lin, Yunyong; Xu, Ruijun (Frontiers in Marine Science, 2025)
IntroductionThe critically endangered hawksbill turtle (Eretmochelys imbricata) is essential for healthy coral reef ecosystems, and its gut microbiota plays a vital role in host nutrition and overall health. A comprehensive understanding of this microbial diversity is crucial for effective conservation, yet current knowledge remains limited. This study aimed to characterize the bacterial taxa present in the fecal samples of hawksbill turtles using culture-dependent methods.MethodsFecal samples from hawksbill turtles were cultured under both aerobic and anaerobic conditions using two distinct bacterial media. A total of 161 bacterial strains were isolated and identified using standard microbiological techniques and 16S rRNA gene sequencing.ResultsThe isolated strains were classified into three phyla: Pseudomonadota (formerly Proteobacteria), Actinomycetota, and Bacillota (formerly Firmicutes). The most frequently identified species were Psychrobacter celer, Shewanella algae, Sulfitobacter pontiacus, Vibrio mytili, Enterococcus hirae, and Psychrobacter maritimus. Ten isolates were identified as potentially representing six novel bacterial species.DiscussionThis study expands our understanding of the microbial diversity associated with hawksbill turtles. It demonstrates the utility of fast and simple culture-dependent approaches for characterizing the microbiota of endangered species, providing a foundation for future research into the roles of these bacteria in turtle health and reef ecosystem function.